2018
DOI: 10.1373/jalm.2017.024554
|View full text |Cite
|
Sign up to set email alerts
|

Development and Population Results of a Fully Automated Homogeneous Assay for LDL Triglyceride

Abstract: Background: Low-density lipoprotein (LDL) is measured by its cholesterol content (LDL-C), but it has been suggested that LDL triglyceride (LDL-TG) may also be related to coronary artery disease risk. LDL-TG can be measured after ultracentrifugation or electrophoresis, but these are labor intensive methods, indicating the need for an automated homogeneous assay. Methods: TG-rich lipoproteins (TRLs), LDL, and HDL were isolated by ultracentrifugation and used to determine optimal characteristics of surfactants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Serum creatinine, liver transaminases, TC, TG, HDL-C, HDL3-C, apoE-HDL-C, direct LDL-C, sdLDL-C, LDL-TG, and RLP-C were measured by automated standardized enzymatic analysis on a Cobas C501 analyzer (Roche Diagnostics, Germany). The specialized lipid assay kits were provided by the Denka-Seiken Corporation (Tokyo, Japan) as previously described 24, 31, 32, 3843) . All specialized lipid assays had within and between run CVs were < 6.0%, and in most cases < 3.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Serum creatinine, liver transaminases, TC, TG, HDL-C, HDL3-C, apoE-HDL-C, direct LDL-C, sdLDL-C, LDL-TG, and RLP-C were measured by automated standardized enzymatic analysis on a Cobas C501 analyzer (Roche Diagnostics, Germany). The specialized lipid assay kits were provided by the Denka-Seiken Corporation (Tokyo, Japan) as previously described 24, 31, 32, 3843) . All specialized lipid assays had within and between run CVs were < 6.0%, and in most cases < 3.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, previous studies concerning the elevated levels of RLP-C and sdLDL-C have been associated with CVs [17][18][19]. In the present study, Spearman's correlation analysis between sdLDL-C and various parameters are shown in the Table 5.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, sdLDL-C levels has the ability to predict CVD better than total LDL-C [18].In addition, the Québec Cardiovascular Study has shown that sdLDL-C is interrelated with an raised risk of CAD in men. [6,7] On the other hand, remnant lipoproteins are rich in TG and the main components include VLDL in the fasting state [20].Obviously, the current study not only con rmed the sdLDL-C concentrations was an independent risk predictor for CVs, but also provided novel information concerning the role of RLP-C in predicting CVs in diabetic patients [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Non-HDL-C was calculated as TC minus HDL-C. Plasma levels of LDL-TG were measured by an automated homogeneous assay (DENKA SEIKEN CO., LTD, Tokyo, Japan) [20]. The measured LDL-TG was with calibration range of 0.0-80 mg/dL.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The measured LDL-TG was with calibration range of 0.0-80 mg/dL. The automated homogeneous LDL-TG method used for our study was validated against the standard sequential density ultracentrifugation method [20]. The concentrations of glucose were measured by enzymatic hexokinase method.…”
Section: Laboratory Analysismentioning
confidence: 99%